Tuai Jaya Enterprise : Adjustable Cassava Harvester / Nur Fatihah Mohamed...[et.al] - Mohamed, Nur Fatihah; Jupery, Nurul Syuhada; Ibrahim, Elmi Afidah; Abdul Kadir, Filzah Hanis; Jamaluddin, Nurul Hedaya; Mohd Naim, Fatin Farhanah (Faculty of Plantation and Agrotechnology, 2017)
Tuai Jaya Enterprise is a partnership business intended to be a manufacturer of adjustable cassava harvester. It is to be located at no, 1117 Blok 6 Felda Lok Heng Timur, 81900 Kota Tinggi, Johor Darul Takzim. This place is chosen because the hire purchase of this area is cheaper compare to others and this area also far from the city where suitable for our manufacturing business. Since it is located at Johor Bharu which the largers cassava producer, therefore is the most strategic areas for producing and marketing the products. The main product that we produce is adjustable cassava harvester that consist of adjustable stick compartment. Our company choose to manufacture adjustable cassava harvester because we want to ease the harvester task instead of using other manual tools. Therefore, we want to produce specific harvester just for cassava. Since cassava is consider high demand raw material for several product such as flour, fresh consumption and even in cosmetic industry. Moreover, many farmers has seen cassava as potential crops to be imported and many large plantations may emerge to produce cassava in mass production. The adjustable cassava harvester were focusing on two region which is Centre and South region of Peninsular Malaysia.